1996
DOI: 10.1093/arclin/11.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Further analyses of clock drawings among demented and nondemented older subjects

Abstract: In a previous article we described a 10-point scoring system (i.e., scale 1) to grade clock drawings to command and copy with hands set for "ten after 11" among demented patients. Alzheimer's subjects (AD) improved from the command to copy conditions, whereas subjects with ischaemic vascular dementia (IVD) did not. To investigate the underlying cognitive deficits responsible for this profile, an additional scale was developed (scale 2) that tallied errors in graphomotor functioning, hand/number placement, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 19 publications
5
96
1
1
Order By: Relevance
“…1). According to several authors [21,88,125,126,201,202], the CDT is able to distinguish different severity levels and clinical forms of dementia, but other authors reported contrasting findings with respect to both issues [65,123,128,131,158]. These deceiving results are probably due to two main factors.…”
Section: Discussionmentioning
confidence: 98%
“…1). According to several authors [21,88,125,126,201,202], the CDT is able to distinguish different severity levels and clinical forms of dementia, but other authors reported contrasting findings with respect to both issues [65,123,128,131,158]. These deceiving results are probably due to two main factors.…”
Section: Discussionmentioning
confidence: 98%
“…Posterior brain regions are essential for drawing tasks, which involve the perception/semantic recall of an image, planning, and the subsequent motor program ming for task execution. CDT usually presents moderate cor relations with other measures of visuospatial proces sing, such as block assembly and figure drawing 12,13 . Patients with vascular lesions, especially those on the posterior right he misphere 1,34 , usually show expressive impairment in the CDT.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these factors, the CDT usually shows significant correlations with measures of visuospatial abilities 12 , execu tive functions 3 , semantic processing 13 , or more global and diffuse cognitive abilities 8 . In Brazil, it is primarily used for the assessment of executive functions 14 .…”
mentioning
confidence: 99%
“…This test was similar to one used by Libon et al [17]. Before the test, we removed the wall clock from the room and asked participants to remove their watches.…”
Section: Clock Drawing Test (Visuospatial Test)mentioning
confidence: 99%